Understanding early maladaptive schemas in autistic and ADHD individuals: exploring the impact, changing the narrative, and schema therapy considerations - Spicer, Liam; DeCicco, Emma; Clarke, Anna; Ambrosius, Rikki; Yalcin, Ozgur (Frontiers in Psychology, 2024)
Autistic/ADHD individuals are increasingly recognised as a valid minority group, with consistent research demonstrating a higher prevalence of co-occurring mental health conditions such as PTSD, anxiety, depression, substance use, and eating disorders among other mental health challenges (Lai et al., 2019; Frank et al., 2018). Due to this, there is increasing focus on the adaptations required for Autistic and ADHD individuals of current therapeutic approaches such as Schema Therapy.Particular emphasis when creating these adaptations needs to include looking at the developmental experiences, social influences, and continued adversity faced by Autistic and ADHD individuals across the lifespan, and how the narrative around Autism and ADHD within psychotherapy in general needs to change. This paper critically examines the role of attachment, unmet needs, and adverse childhood experiences in Autistic and ADHD individuals and the subsequent impact on schema development and maintenance and mental health. This will include an overview of the current literature in this area, reconsideration of understandings of Autism and ADHD, particular therapeutic considerations and adjustments and importantly discussion around the wider societal changes that need to occur to prevent schema development and reinforcement across the lifespan.